Boron in groundwater of the Island of Cyprus - Eleftheriou, Polyvios (My University, 2001)
Boron can be found in high concentrations in the groundwater of the Island of Cyprus, especially in the central part of the island. Boron in high concentrations is of major concern due to its toxicity to both animals and irrigated plants. The origin of the phenomenon is not very well understood and is usually explained as remains of seawater. This work quantifies the boron content through analytical techniques and provides more information on the levels found.
Keywords: Boron; Groundwater; Irrigation; Seawater; Open access publishing